Religiosity and gender equality: comparing natives and Muslim migrants in Germany - Diehl, Claudia; Koenig, Matthias; Ruckdeschel, Kerstin (Ethnic and racial studies, 2009)
In European public debates, Islam is often described as an impediment to gender equality. By using data from surveys conducted in Germany, we analyse the role of high levels of individual religiosity in explaining Turks’ and Germans’ approval of gender equality and the way Turkish and German couples share household tasks. Results suggest that, for both groups, individuals with strong religious commitments are less likely than secular individuals to hold egalitarian gender role attitudes. At the behavioural level, this correlation between religiosity and gender egalitarianism only holds true for Turkish respondents. Furthermore, strong religious commitments contribute to generational stability in attitudinal and behavioural gender-traditionalism among Turks. However, when explaining Germans’ more egalitarian gender-related attitudes and behaviours, religiosity turns out to be just one factor among others - and not a particularly important one. Further research is needed to disentangle the different cultural and religious aspects of Muslim migrants’ attitudes and behaviours.
Gesehen am 08.06.2021
Keywords: Deutschland